A randomized controlled trial of dance exergaming for exercise training in overweight and obese adolescent girls. Issue 2 (26th February 2016) - Staiano, A. E.; Marker, A. M.; Beyl, R. A.; Hsia, D. S.; Katzmarzyk, P. T.; Newton, R. L.
Summary: Background: Structured exergaming with prescribed moderate intensity physical activity has reduced adiposity among adolescents. The extent to which adolescents reduce adiposity when allowed to self‐select intensity level is not known. Objective: The objective of the study was to examine the influence of exergaming on adolescent girls' body composition and cardiovascular risk factors. Methods: This randomized controlled trial assigned 41 overweight and obese girls aged 14 to 18 years to group‐based dance exergaming (36 h over 3 months) or to a self‐directed care control condition. Body size and composition were measured by anthropometry, dual‐energy X‐ray absorptiometry [%fat and bone mineral density BMD] and magnetic resonance imaging. Cardiovascular risk factors included blood pressure, cholesterol, triglycerides, glucose and insulin. Results: Attrition was 5%. Using analysis of covariance controlling for baseline value, age and race, there were no significant condition differences. Per protocol (attended >75%), the intervention group significantly decreased abdominal subcutaneous adiposity and increased trunk and spine BMD ( p s < 0.05). Per protocol (>2600 steps/session), the intervention group significantly decreased leg %fat and decreased abdominal subcutaneous and total adiposity ( p s < 0.05). Conclusion: Exergaming reduced body fat and increased BMD among those adolescent girls who adhered. Further research is required before exergaming is recommended in clinical settings.